Recent developments in the design and synthesis of benzylpyridinium salts: Mimicking donepezil hydrochloride in the treatment of Alzheimer’s disease - Sepehri, Saghi; Saeedi, Mina; Larijani, Bagher; Mahdavi, Mohammad (Frontiers in Chemistry, 2022)
Background: Alzheimer’s disease (AD) is an advanced and irreversible degenerative disease of the brain, recognized as the key reason of dementia among elderly people. The disease is related to the reduced level of acetylcholine (ACh) in the brain that interferes with memory, learning, emotional and behavior responses. Deficits in cholinergic neurotransmission are responsible for the creation and progression of numerous neurochemical and neurological illnesses such as AD. Aim: Herein, focusing on the benzyl-pyridinium salts mimicking the structure of donepezil hydrochloride as a FDA approved drug in the treatment of AD, their synthetic approaches and inhibitory activity against cholinesterases (ChEs) were discussed. Also, molecular docking results and structure-activity relationship (SAR) as the most significant concept in drug design and development were considered to introduce potential lead compounds. Key scientific concepts: AChE plays a chief role in the end of nerve impulse transmission at the cholinergic synapses. In this respect, inhibition of AChE has been recognized as a key factor in the treatment of AD, Parkinson’s disease, senile dementia myasthenia gravis and ataxia. A few drugs such as donepezil hydrochloride are prescribed for the improvement of cognitive dysfunction and memory loss caused from AD. Donepezil hydrochloride is a piperidine comprising compound, identified as the well-known member of the second generation of AChE inhibitors. It was established to treat AD when it was assumed that the disease is associated with a central cholinergic loss in the early 1980s. In this review, synthesis and anti-ChE activity of a library of benzyl-pyridinium salts were reported and discussed based on the SAR studies looking for the most potent substituents and moieties which are responsible for inducing desired activity even more potent than donepezil. It was found that linking heterocyclic moieties to the benzyl-pyridinium salts leads to the potent ChE inhibitors. In this respect, this review focused on the recent reports on benzyl-pyridinium salts and addressed the structural features and SARs to get an in-depth understanding of the potential of this biologically improved scaffold in drug discovery of AD.